2014
DOI: 10.1017/s0950268814003100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus in slaughter-age pigs in Scotland

Abstract: The prevalence of anti-HEV isotype-specific antibodies and viraemia were investigated in serum samples collected from slaughter-age pigs (aged 22-24 weeks) from 23 farms in Scotland. Of 176 serum samples tested, 29·0% (n = 51) were anti-HEV IgG positive, 36·9% (n = 65) anti-HEV IgA positive and 29·0% (n = 51) anti-HEV IgM positive. Overall seroprevalence (anti-HEV IgG+ and/or IgA+ and/or IgM+) was 61·4% (n = 108). HEV RNA was detected in 72/162 serum samples (44·4%). Partial sequence of ORF2 (98 nt) was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 14 publications
3
44
2
1
Order By: Relevance
“…88,89 HEV infection has been identified in more than 80% of some pig herds in the USA, Canada and in the UK (England), 90,91 although Scottish herds have a lower seroprevalence of around 62%. 92 In a more recent report on English and Northern Irish pigs, 93% of slaughter age animals were seropositive. 90 In the West of Scotland, 92% of tested wild caught mussels were PCR positive for HEV and consumption of undercooked/raw shellfish is another viable route of transmission.…”
Section: Genotypementioning
confidence: 97%
“…88,89 HEV infection has been identified in more than 80% of some pig herds in the USA, Canada and in the UK (England), 90,91 although Scottish herds have a lower seroprevalence of around 62%. 92 In a more recent report on English and Northern Irish pigs, 93% of slaughter age animals were seropositive. 90 In the West of Scotland, 92% of tested wild caught mussels were PCR positive for HEV and consumption of undercooked/raw shellfish is another viable route of transmission.…”
Section: Genotypementioning
confidence: 97%
“…Crossan et al separately tested the presence of the different types of anti-HEV antibodies in Scotland and reported that, of 176 serum samples tested, 29% ( n  = 51) were anti-HEV IgG-positive, 36.9% ( n  = 65) anti-HEV IgA-positive and 29% ( n  = 51) anti-HEV IgM-positive. Overall seroprevalence (anti-HEV IgG+ and/or IgA+ and/or IgM+) was 61.4% ( n  = 108) [16]. In the same region and period, individual HEV seroprevalence was found by Grierson et al to be even higher; they reported that 584 out of 629 pigs (92.8%) had anti-HEV antibodies at the time of slaughter [17].…”
Section: Hev Prevalence In Farmed Pigsmentioning
confidence: 99%
“…In Europe, high HEV seroprevalence has been detected in swine from Spain [143, 144], Italy [145147], Norway [29], Denmark [148], UK [149, 150], Estonia [151], Germany [152, 153], or Switzerland [154, 155]. According to the seroprevalence data, 76% to 98% of Spanish swine farms have evidence of HEV presence [143, 144, 156, 157].…”
Section: Hev In Animalsmentioning
confidence: 99%
“…On the other hand, RNA has been found in feces, liver, bile, and cecal content of animals at slaughter age, representing a risk of entrance of HEV into the food chain [149, 150, 157, 160]. Casas et al [160] identified the virus in liver or bile of 3 animals at slaughter age 3 months after the first reports of their infection.…”
Section: Hev In Animalsmentioning
confidence: 99%
See 1 more Smart Citation